Angiogenesis in liver cirrhosis and hepatocellular carcinoma - Amarapurkar Anjali; Vibhav; Kim V (Wolters Kluwer Medknow Publications, 2008)
Background: Angiogenesis has been well documented in hepatocellular carcinoma (HCC). As liver cirrhosis is considered preneoplastic condition, the aim of this study was to evaluate the process of angiogenesis using CD 34 as an endothelial cell marker in normal liver, cirrhosis and HCC. Materials and Methods: A total of 111 cases were included in this study, which consisted of 30 cases each of normal liver and cirrhosis that were all autopsy cases. Twenty-one cases of HCC included 10 autopsy specimens, nine surgically resected specimens and two liver biopsies. Remaining were 30 cases of metastasis to the liver, which included 20 autopsy specimens, one surgically resected specimen and nine liver biopsies. The patients were between the age range from 17 to 80 years with 70 males and 11 females. Paraffin-embedded liver sections of all these cases were stained routinely by hematoxylin-eosin stain, while immunohistochemistry for CD 34 was performed for expression of endothelial cells. The positivity of CD 34 staining was evaluated by counting in 10 high-power field, grading was done from 0 to 4 and compared between normal liver, cirrhosis and HCC and metastasis. Results: CD 34 was positive in 16/30 (53.3%) cases of cirrhosis, 18/21 (85%) cases of HCC and 26 (86.6%) of metastasis to the liver. None of the normal liver showed any positivity. Grade 3 to 4 positivity was seen in 4/16 (25%) and 13/18 (72%) cases of cirrhosis and HCC, respectively. Amongst these, 10 were moderately differentiated, one well differentiated and rest two were fibrolamellar and sarcomatoid variants of HCC. Conclusion: Over expression of endothelial cell marker CD 34 with gradual progression was found from normal liver to cirrhosis to HCC and metastasis. Understanding of this process of angiogenesis might help in the design of efficient and safe antiangiogenic therapy for these liver disorders.